Board Characteristics and Firm Performance of Public Listed Companies in Malaysia - H-Sufi, Faisal Abukar (2012)
The study aims to investigate the influence of board characteristics on firm performance before and after the revised of Malaysian Code of Corporate Governance 2007. The data for study gathered from two years, 2006 and 2010, that represent before and after the revised version of Malaysian Code of Corporate Governance. Regression analysis was performed to examine factors influencing firm performance such as board size, outside directors, family members on the board,audit committee size,audit committee independent, control variables such as firm size, leverage, and firm performance. In addition, firm performance was measured by return on asset (ROA). Using a sample of 80 companies for both years, the result showed that none of the board characteristics, board size, independent directors, family members on the board, audit committee size, audit committee independent, have significant relationship with firm performance. However, the control variables, firm size and leverage, have significantly positive and negative correlation with firm performance in both years.